2005
DOI: 10.1002/pola.21216
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition–fragmentation chain transfer graft copolymerization of styrene and m‐isopropenyl‐α,α′‐dimethylbenzyl isocyanate from polypropylene lanterns: Solid phases for scavenging applications

Abstract: The γ‐initiated reversible addition–fragmentation chain transfer mediated free‐radical graft copolymerization of styrene and m‐isopropenyl‐α,α′‐dimethylbenzyl isocyanate (TMI) from a polypropylene (PP) solid phase was performed with cumyl phenyldithioacetate (CPDA) as the chain‐transfer agent. The initial CPDA concentration was 8 × 10−3 mol L−1. Polymerizations were performed with a dose rate of 0.18 kGy h−1 at the ambient temperature. Initial comonomer mixtures with 15, 30, and 50 mol % TMI were used. Dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…[11] Smith et al observed that the extent of grafting of an RGD peptide onto polyNAS decreased with increasing pH value and temperature owing to promotion of hydrolysis. [11] Cline and Hanna have noted that the reactivity of various amines towards aminolysis of p-nitrobenzoyl-Nhydroxysuccinimide in anhydrous dioxane correlated strongly with the basicity of the amino group, though steric hindrance within the investigated set of amines caused certain deviations [11,16] diNAS [8] NAS [18] NMAS [9,15,19] NAS [20] NSVB [20] NAS [4,13] NMAS [21,22] NSVB [23] NNHS [24] PFA [6] PFMA [6] PFVB [25] PFMA [26] NPF [7] NPA [27] NPMA [28] NPA [29] NPMA [30] MAPTT [10] 3 MA [17] MA [31] MA [32] MVI [17,33] VI [33] TMI [34] VDM [35,36] VDM [37] VDM [38] VPDMO [38] IDMO [38] GMA [39] GMA [40] 4-ES [41] GMA [42] GA [43] GMA …”
Section: Reviews 50mentioning
confidence: 97%
“…[11] Smith et al observed that the extent of grafting of an RGD peptide onto polyNAS decreased with increasing pH value and temperature owing to promotion of hydrolysis. [11] Cline and Hanna have noted that the reactivity of various amines towards aminolysis of p-nitrobenzoyl-Nhydroxysuccinimide in anhydrous dioxane correlated strongly with the basicity of the amino group, though steric hindrance within the investigated set of amines caused certain deviations [11,16] diNAS [8] NAS [18] NMAS [9,15,19] NAS [20] NSVB [20] NAS [4,13] NMAS [21,22] NSVB [23] NNHS [24] PFA [6] PFMA [6] PFVB [25] PFMA [26] NPF [7] NPA [27] NPMA [28] NPA [29] NPMA [30] MAPTT [10] 3 MA [17] MA [31] MA [32] MVI [17,33] VI [33] TMI [34] VDM [35,36] VDM [37] VDM [38] VPDMO [38] IDMO [38] GMA [39] GMA [40] 4-ES [41] GMA [42] GA [43] GMA …”
Section: Reviews 50mentioning
confidence: 97%
“…[238] Other papers cover RAFT polymerization of AA/65 from a PVDF surface previously irradiated with an electron beam [115] and graft copolymerization from a PP surface was achieved by gamma-irradiation of a solution of styrene and 1-(2-isocyanatopropan-2-yl)-3-(propen-2-yl)benzene and 38 in the presence of a PP 'lantern'. [239] Several papers report the use of RAFT polymerization to prepare a backbone polymers/macroinitiator for comb polymer synthesis. Poly(N-phenyl maleimide-co-(4-chloromethylstyrene)) was prepared by RAFT copolymerization with 7 and used as a macroinitiator for ATRP of styrene (CuCl/2,2 -bipyridine catalyst) to form poly(N -phenyl maleimide-co-4-chloromethylstyrene)-combpolystyrene.…”
Section: Grafting-from Processesmentioning
confidence: 99%
“…We applied ginitiation and RAFT [103] to graft low polydispersity polymers (styrene and m-isopropenyl-a,a 0 -dimethyl benzyl isocyanate) from poly(propylene) lanterns. [104,105] These studies demonstrate that two distinct regimes of grafting exist: i) the grafting layer regime, in which the surface is not yet completely covered with polymer chains, and ii) a regime in which a second polymer layer is formed. In this second regime, the surface is effectively covered with polymer chains (of well-defined length) and new polymer chains are started by PS radicals from already grafted chains.…”
Section: Macromolecular Design On the Surfaces Of Microspheresmentioning
confidence: 99%